The idea of human rights - Beitz, Charles R. (Oxford University Press, 2011)
Human rights have become one of the most important moral concepts in global political life over the last 60 years. Charles Beitz, one of the world's leading philosophers, offers a compelling new examination of the idea of a human right.--. - Source other than Library of Congress.